Pendampingan Komunitas Petani Jeruk dalam Memetakan Kebutuhan Menuju Desa Wisata Modongan Kabupaten Mojokerto - N. Agus Sunarjanto; Yohanes Harimurti; Agnes Utari Widyaningdyah; Yohanes Bayu Kusnanto; Lydia Ratnasari Tejosaputra (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This research and community service activity was carried out at the Siam orange farmer group in Modongan village, Sooko sub-district, Mojokerto regency. This activity is the initial activity carried out in mapping the needs of farmers. The approach taken is to conduct focus group discussions that place the facilitator not as an informant but as a moderator and motivator. With the role of the facilitator, the problems faced are the result of reflection from the village community. This problems mapping will be analyzed by conducting a component and SWOT (strengths, weaknesses, opportunities, and threats) analysis. The results of this analysis will then be followed up into strategies for transforming the village of Modongan into an agriculture-based tourism village in various series of community service activities; such as strengthening village institutions and mentoring through learning resources from other villages that have successfully implemented the concept of a tourist village